Determination of Wavelength of He-Ne Laser and Diode Laser Using Single Slit Diffraction Method - Purwaningsih, Sri; Falah, Hebat Shidow; Lestari, Neneng; Sartikasari, Dwi; Yuversa, Edi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This research aims to investigate/determine the value of the laser wavelength produced by He-Ne lasers and Diode lasers using the concept of diffraction at a single slit. The gaps used consist of three types of gaps which have gaps with a width of 0.12 mm, 0.24 mm, and 0.48 mm. Experimental results show that the wavelength of He-Ne laser light ranges from 640 nm to 646 nm. Meanwhile, the wavelength of He-Ne laser light ranges from 640 nm to 686.67 nm. Based on the results obtained, it can be concluded that it is proven that the wavelength calculated using the single slit diffraction method is in the range of values for lasers that emit red light.